Effects of cimetidine and N-acetylcysteine on paraquat-induced acute lung injury in rats: a preliminary study. Issue 8 (26th November 2018) - Farshad, Omid; Heidari, Reza; Zare, Farshid; Jamshidzadeh, Akram; Ebrahimi, Melika; Zamiri, Mohammad Javad; Zaker, Ladan; Ommati, Mohammad Mehdi
Abstract: Lung injury in rats challenged with paraquat at 20 mg kg −1 body weight was histopathologically evident by inflammation, hemorrhage, and vascular congestion. Increased levels of reactive oxygen species and lipid peroxidation, decreased glutathione content, and lower tissue antioxidant capacity was found. The effects of N-acetylcysteine and cimetidine, a well-known potent inhibitor for organic cation transport, were examined. Lung injury was attenuated by N-acetylcysteine but not by cimetidine. The findings are consistent with the assumption that beneficial effects of N-acetylcysteine administration in paraquat-challenged animals might be linked to its ability for preserving the cellular redox environment and preventing oxidative stress, while cimetidine might even hasten paraquat-induced lung injury. On the other hand, the effects of cimetidine on paraquat-induced lung injury underline the importance of future studies on the role of transporters in this complication.